UPAYA GURU PAI DALAM MEMBENTUK SIKAP RELIGIUS SISWA MELALUI KEGIATAN UBUDIYAH DI SMPI AL-MAARIF 01 SINGOSARI - Dyah Latifatul Husna; Ach. Faisol; Mutiara Sari Dewi (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
This research was conducted to find out more about the religious activities in SMPI AlMaarif 01 Singosari, in order to form religious attitudes in students. Because as we know there are many forms of juvenile delinquency that have recently occurred. Education is something that is important for humans in life. Education is a necessity that must be fulfilled in the life of the nation and state. Education will help create and improve the quality of good and superior human resources. This is why the existence of religious activities in schools greatly affects the attitudes of students in their daily lives. In addition, the role of teachers and parents is also very necessary in order to develop students' religious attitudes. A teacher has an important task in preparing the new generation of the nation's successors through general sciences and religious studies. The condition of technological progress as it is today, it is very necessary for us as educators to emphasize religious teachings to students. Because if students are used to doing religious activities they will always get used to doing good things in everyday life. Basically, this can be used as a guideline for the continuation of a good way of life, so that students always walk in goodness.